Association Between a Genetic Variant Related to Glutamic Acid Metabolism and Coronary Heart Disease in Type 2 Diabetes - Qi, Lu (2013)
IMPORTANCE: Diabetes is associated with an elevated risk of coronary heart disease (CHD). Previous studies have suggested that the genetic factors predisposing to excess cardiovascular risk may be different in diabetic and non-diabetic participants. OBJECTIVE: To identify genetic determinants of CHD that are specific to diabetic patients. DESIGN, SETTING, AND PARTICIPANTS: We studied five independent sets of CHD cases and CHD-negative controls from the Nurses Health Study (NHS; enrolled in 1976 and followed through 2008), Health Professionals Follow-up Study (HPFS; enrolled in 1986 and followed through 2008), Joslin Heart Study (enrolled in 2001-2008), Gargano Heart Study (enrolled in 2001-2008), and Catanzaro Study (enrolled in 2004-2010). Included were a total of 1,517 CHD cases and 2,671 CHD-negative controls, all with type 2 diabetes. Results in diabetic patients were compared with those in 737 non-diabetic CHD cases and 1,637 non-diabetic CHD-negative controls from the NHS and HPFS cohorts. EXPOSURE: 2,543,016 common genetic variants occurring throughout the genome. MAIN OUTCOME: CHD defined as fatal or non-fatal myocardial infarction, coronary artery bypass grafting, percutaneous transluminal coronary angioplasty, or angiographic evidence of significant stenosis of the coronary arteries. RESULTS: We identified a variant on chromosome 1q25 (rs10911021) consistently associated with CHD risk among diabetic participants with an odds ratio of 1.36 (95% confidence interval [CI] 1.22-1.51, P=2×10(−8)). No association between this variant and CHD was detected among non-diabetic participants (OR=0.99, P=0.89), consistent with a significant gene-by-diabetes interaction on CHD risk (P=2×10(−4)). As compared to protective allele homozygotes, rs10911021 risk allele homozygotes were characterized by a 32% decrease in the expression of the neighboring glutamate-ammonia ligase (GLUL) gene in human endothelial cells (P=0.0048). They also showed a decreased ratio between plasma levels of γ-glutamyl cycle intermediates pyroglutamic and glutamic acid in two independent studies (P=0.029 and P=0.003, respectively). CONCLUSIONS AND RELEVANCE: A SNP was identified that was significantly associated with CHD among persons with diabetes but not in those without diabetes. This SNP was functionally related to glutamic acid metabolism, suggesting a mechanistic link.